And What About the Pharmacist?: On the Position of the Provider of Lethal Drugs in Dutch Euthanasia Practice - Buijsen, Martin (Cambridge quarterly of healthcare ethics, 2020)
In the Netherlands, euthanasia has been decriminalized. Termination of life on request and assisted suicide are criminal offences under Dutch law; but if physicians comply with the due care requirements of the Euthanasia Act and report their actions in the manner prescribed by law, they will not be prosecuted. One of the requirements relates to the act of euthanasia itself. If this is to be performed with due medical care, the physician relies on the services of a pharmacist. However, the responsibilities of the pharmacist with respect to euthanasia are not laid down in law. At present, Dutch pharmacists have to make do with professional rules that do not offer adequate solutions for the problems that may arise when euthanasia is performed.